Dynamics of cerebrospinal fluid in correction of degenerative lumbosacral stenozis during the postoperative period in dogs - Ilya F. Vilkowysky (RUDN Journal of Agronomy and Animal Industries, 2022)
Dynamics of cerebrospinal fl parameters in postoperative period during correction of degenerative lumbosacral stenosis in dogs is an important diagnostic aspect that allows monitoring changes in the state of animals after surgery. An accurate analysis of cerebrospinal fl id provides a wide range of information about the patients neurological health. The assessment should consist of macroscopic, quantitative and microscopic analyses. Сell count is the most important and potentially sensitive indicator of disease. The aim of this study was to determine changes in the cerebrospinal fluid during the postoperative period in the correction of degenerative lumbosacral stenosis. In the study, there were 9 dogs of various breeds, aged from 2 to 8 years (experimental group), the indicators of cerebrospinal fluid and peripheral blood of 3 healthy outbred dogs obtained as a result of medical examination at the age of up to 5 years were used as a control. Surgical intervention was carried out according to the B.P. Meij, N. Bergknut, which consists in dorsal access to the L7-S 1 vertebral arches, soft tissue dissection, dissection of the dorsal ligament, formation of channels in the cranial articular processes of S 1, L7. From each animal, three liquorograms were taken for examination three times on days 1-3 after surgery, on days 12-15 and 27-30 after surgery. The study of cerebrospinal fluid was performed within 30 minutes after taking. As a result of the data obtained, it was found that the cellular composition of the liquor of dogs in the postoperative period of correction of lumbosacral stenosis was within the physiological norm, erythrocytes in the cerebrospinal fluid were not detected. The number of nucleated cells in operated dogs was the highest on days 1-3 after surgery. On the 12th-15th day after the operation, cytosis in the experimental and control groups of animals was 1.27 cells/l more. On days 27-30 after surgery, cytosis in dogs in the experimental group was lower by 0.45 cells/l compared to the control. Analysis of cerebrospinal fluid can help in the diagnostic assessment of the condition of animals in the postoperative period. However, it should be borne in mind that results are rarely specific to any particular condition and should be interpreted in the light of clinical and additional diagnostic findings.